Cardiac remodeling induced by 13-cis retinoic acid treatment in acne patients - Soriano, Eline A. [UNESP] (2013)
Background: Currently, 13-cis-retinoic acid (13-cis-RA) is the most effective therapy for acne. Isotretinoin, a first-generation synthetic 13-cis-RA compound, is associated with numerous adverse effects. To investigate the cardiac effects of 13-cis-RA, acne patients receiving 13-cis-RA were studied. Methods: Twenty male patients with acne were enrolled in the study. Patients were treated with a dose of 0.5 mg/kg/d of isotretinoin. All participants were assessed prior to treatment and after 10 weeks of therapy with Doppler-echocardiogram. Results: Patients showed reductions in right atrium vertical diameter, left atrium longitudinal diameter, left atrium volume and left ventricular diastolic diameter over the course of treatment. Significant increases in interventricular septum diastolic thickness, posterior wall diastolic thickness, relative wall relative thickness and left ventricle (LV) mass were observed. The LV mass index showed an increase in ventricular mass and a decrease in the cavity size. Examining LV systolic function, a decrease was observed for the cardiac index. Conclusion: In this study, 10 weeks of 13-cis-RA therapy at a dose of 0.5 mg/kg/d was found to promote concentric-type heart remodeling due to the occurrence of two associated events: heart hypertrophy and hypovolemia. © 2011 Elsevier B.V. All rights reserved.